Simultaneous separation/preconcentration of ultra trace heavy metals in industrial wastewaters by dispersive liquid–liquid microextraction based on solidification of floating organic drop prior to determination by graphite furnace atomic absorption spectrometry - Mirzaei, Mohammad; Behzadi, Mansoureh; Abadi, Nasrin Mahmoud; Beizaei, Alieh (Journal of hazardous materials, 2011)
In the present work, an efficient microextraction method was applied to separation and preconcentration of Ni(II), Co(II), Pb(II) and Cr(III). This method is dispersive liquid–liquid microextraction based on solidification of floating organic drop, which overcomes the most important problems of each aforementioned technique. The influences of analytical parameters, including pH, extraction solvent volume, disperser solvent type and its volume, concentration of chelating agent, salt effect and extraction time on the quantitative recoveries of nickel, cobalt, lead and chromium ions were investigated. Under the optimized conditions, the limits of detection were 0.2ngL−1 for Cr and 1.3ngL−1 for Co, Ni and Pb, with a preconcentration factor of 800 times. The relative standard deviations of 6.2% at 6.0ngL−1 of Cr and 7.2% at 10ngL−1 of Co, Ni and Pb were obtained (n=7). The proposed method was successfully applied for the analysis of ultra trace metals in water and wastewater samples.